Maria - Bartoli, Cecilia 1966-; Vengerov, Maksim A. 1974-; Albelo, Celso 1975-; Pisaroni, Luca 1975-; Hämmerli, Jürg 1958-; Hämmerli, Jürg 1958-; Fischer, Ádám 1949- (Decca, 2007)
"A tribute to the extraordinary life of Maria Malibran, the first female superstar in music history."